PENGARUH DOSIS PUPUK UREA DAN UMUR PANEN YANG BERBEDA TERHADAP KANDUNGAN NUTRISI FODDER JAGUNG (Zea mays) HIDROPONIK: THE EFFECT OF DIFFERENT UREA FERTILIZER DOSES AND HARVEST AGE ON NUTRITION CONTENTS OF HYDROPONIC CORN FODDER - Oktaria, Vivi Dwi; Irsyammawati, Artharini; Subagiyo, Ifar (Tropical Animal Science, 2023)
This experiment aimed at determining the effect of doses of urea fertilizer and harvest age on the Dry Matter (DM), Crude Fiber (CF), Crude Protein (CP) and Organic Matter (OM) contents of corn fodder under hydroponic system. The planting experiment employed Factorial Completely Randomized Design (FCRD) with 4 main treatments i.e. P0 (zero levels of urea fertilizer), P1 (0.15 gram urea/L), P2 (0.3 gram urea/L), P3 (0.45 gram urea/L) and 3 sub-treatments i.e. the harvest age of 7 days, 14 days and 21 days. The treatments were replicated 3 times. The variables measured include Dry Matter (DM), Organic Matter (OM), Crude Protein (CP) and Crude Fibre (CF) of the corn fodder. Collected data were subjected to analysis of variance and if significant effects of treatments were identified then Duncan’s Multiple Range Test was employed. It was found that the interaction of the treatments did not significantly affect (P>0.05) all the variables measured. Doses of urea fertilizer only gave a highly significant effect (P<0.01) on CP content whilst harvest age gave highly significant effect (P<0.01) to all variables measured. It can concluded that adding doses of urea gave effect only on CP content of corn fodder under hydroponic system and harvest age gave effect on Dry Matter (DM), Organic Matter (OM), Crude Protein (CP) and Crude Fibre (CF) of the fodder produced. Harvest age of 14 days is suggested as it gave the highest DM, OM and CP content with the lowest CF content.